Hydroxyurea Treatment for Sickle Cell Disease - Martin H. Steinberg (The Scientific World Journal)
High fetal hemoglobin (HbF) levels inhibit the polymerization of sickle hemoglobin (HbS) and reduce the complications of sickle cell disease. Pharmacologic agents that can reverse the switch from γ- to β-chain synthesis — γ-globin chains characterize HbF, and sickle β-globin chains are present in HbS — or selectively increase the proportion of adult erythroid precursors that maintain the ability to produce HbF are therapeutically useful. Hydroxyurea promotes HbF production by perturbing the maturation of erythroid precursors. This treatment increases the total hemoglobin concentration, reduces the vaso-occlusive complications of pain and acute chest syndrome, and attenuates mortality in adults. It is a promising beginning for pharmacologic therapy of sickle cell disease. Still, its effects are inconsistent, trials in infants and children are ongoing, and its ultimate value — and peril — when started early in life are still unknown.